2018
DOI: 10.1002/pld3.95
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing postgraduate training in the plant sciences: T‐training defined through modularity, customization, and distributed mentorship

Abstract: The Plant Science Research Network ( PSRN ) comprises scientific societies and organizations with a mission to build and communicate a consensus vision of the future of plant science research, education, and training. This report enumerates a set of far‐reaching recommendations for postgraduate training that emerged from workshops held in October 2016 and September 2017. These recommendations broaden and deepen the T‐training concept presented in the Decadal Vision for Plant Science, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…3 New opportunities in plant science‐related jobs 4 underscore the need to rethink career expectations and to retool training paradigms to prepare researchers for careers beyond academia. The PSRN previously published recommendations for postgraduate training using a subway network metaphor to illustrate three main principles: flexible pathways, multiple career destinations, and the possibility of multiple on‐ and off‐ramps (Henkhaus, Taylor, Greenlee, Sickler, & Stern, 2018). The PSRN further emphasized the need for trainee‐centric approaches that offer trainees more control over their professional development through modular customization and a new mentoring model to help them with prioritization and focus.…”
Section: Recommendationsmentioning
confidence: 99%
“…3 New opportunities in plant science‐related jobs 4 underscore the need to rethink career expectations and to retool training paradigms to prepare researchers for careers beyond academia. The PSRN previously published recommendations for postgraduate training using a subway network metaphor to illustrate three main principles: flexible pathways, multiple career destinations, and the possibility of multiple on‐ and off‐ramps (Henkhaus, Taylor, Greenlee, Sickler, & Stern, 2018). The PSRN further emphasized the need for trainee‐centric approaches that offer trainees more control over their professional development through modular customization and a new mentoring model to help them with prioritization and focus.…”
Section: Recommendationsmentioning
confidence: 99%
“…To support graduate student mental health and well‐being, it has been suggested that graduate programming support self‐care to promote mental health and to protect from mental illness (Evans et al, 2018; Henkhaus et al, 2018). But, there are a number of potential challenges for graduate programming to achieve this because there are few concrete examples of effective strategies.…”
Section: The Challenge For Graduate Programsmentioning
confidence: 99%
“…This awareness has led to a call for strategies to “improve the culture of mental health and well‐being among graduate students” (Mousavi et al, 2018). Organizations such as the Plant Science Research Network (PSRN) have prioritized trainee well‐being to become one of its core principles (Henkhaus, Taylor, Greenlee, Sickler, & Stern, 2018). With this, the PSRN recognized that a shift in training culture is needed (Henkhaus et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report from another NSF‐funded RCN, the Plant Science Research Network, advocates for increased empowerment of trainees to personalize their Ph.D. training program, and proposes a modular approach that could, e.g., facilitate incorporation of training in both wet bench and analytical skills, and would be conducted under the guidance of a mentoring team (Henkhaus, Taylor, Greenlee, Sickler, & Stern, ). Such a shift in training paradigms might also help to create a more inclusive environment and promote workforce diversity.…”
Section: Big Visions: Training the Omics Scientistmentioning
confidence: 99%